Comparison of Leukocyte, Neutrophil, and Lymphocyte Levels in Child Patients that Experienced Breathlessness with COVID-19 and Non-COVID-19 (2020–2021) in Medan, Indonesia - Wijaya, Hendri; Pitaloka, Ayodhia; Lubis, Ivnke; Amelia, Rina (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: COVID-19 is a disease caused by severe acute respiratory syndrome coronavirus-2. Various risk factors affect the morbidity and mortality of COVID-19, such as age, gender, ethnicity, comorbid conditions, and laboratory parameters. Clinical manifestations of COVID-19 in children are asymptomatic mild degrees or with acute upper respiratory tract symptoms and moderate degrees with clinical pneumonia. In the course of the COVID-19 pandemic, several biomarkers are needed that can be useful in risk stratification to predict the severity and fatality of COVID-19. Several biomarkers are used as markers of disease progression to a critical degree, such as leukocytes, lymphocytes, platelets, interleukin-6, and serum ferritin. Increased leukocytes and neutrophils and decreased lymphocytes are associated with severity and mortality in COVID-19. Laboratory findings in children with COVID-19 include decreased lymphocytes, leukopenia, and increased procalcitonin. In severe COVID-19, children often have abnormal laboratory parameters that suggest a systemic inflammatory response. AIM: This study aims to compare leukocytes, neutrophils, and lymphocytes levels in children with the complaints of shortness of breath with COVID-19 and non-COVID-19 pediatric patients. MATERIALS AND METHODS: This study is an analytic study with a cross-sectional approach to pediatric patients treated in Haji Adam Malik General Hospital Medan with the complaints of shortness of breath. Patient data were assessed based on the characteristic values of hemoglobin, leukocytes, neutrophils, lymphocytes, and COVID-19 polymerase chain reaction results and then analyzed using SPSS for Windows software. The study samples were 276 patients, with 43 confirmed positive COVID-19 patients and 233 negative patients. The source of this research data is data from the patient’s medical record for 1 year (2020–2021). RESULTS: The statistical analysis results found differences in the levels of leukocytes, neutrophils, and lymphocytes in children diagnosed with COVID-19 and non-COVID-19 (p < 0.05). However, there was no difference in hemoglobin levels in children who were congested with COVID-19 and non-COVID-19 (p > 0.05). CONCLUSION: These results are consistent with several cases and previous studies where the levels of leukocytes, neutrophils, and lymphocytes can be used as a detection tool and a diagnostic and prognostic tool in COVID-19 patients.